A protective ceramic coating to improve oxidation and thermal shock resistance on CrMn alloy at elevated temperatures. Issue 3 (April 2015) - Shan, X.; Wei, L.Q.; Zhang, X.M.; Li, W.H.; Tang, W.X.; Liu, Y.; Tong, J.; Ye, S.F.; Chen, Y.F.
Abstract: A protective ceramic coating was synthesized on CrMn alloy substrate by the slurry–spraying method. The thermal shock resistance and anti-oxidation properties of the coating were studied within a wide range of temperature in air atmosphere. The specimens were characterized by X-ray diffraction (XRD), metallurgical microscopy and scanning electron microscopy–energy dispersive X-ray spectroscopy (SEM–EDX). The results showed that 53 times of thermo cycling test by air cooling and nine times by water quenching can be acquired before the coating failed. In the oxidation tests, compared with the bare sample, the as-synthesized coating reduced the weight gain of the CrMn alloy from 27.99 mg/cm 2 to 7.16 mg/cm 2 at 900 °C isothermal oxidation (540 min). At temperatures higher than 900 °C, the ceramic coating diminished the oxidation loss significantly. The compact ceramic layer, mainly formed of BaCrO4, Cr2 O3, and SiO2, decreased the element diffusion velocity including O and Fe. The thermal shock resistance was greatly enhanced by the hook-like ceramic which inlayed at the interface of the steel substrate and by the good match of the coefficient of thermal expansion (CTE) between the coating and substrate. The proposed protective mechanism of the anti-oxidation and thermal shock resistance properties of the coating is also discussed in this paper.